Cultural universality and specificity of student engagement in school: The results of an international study from 12 countries. (22nd May 2015) - Lam, Shui‐fong; Jimerson, Shane; Shin, Hyeonsook; Cefai, Carmel; Veiga, Feliciano H.; Hatzichristou, Chryse; Polychroni, Fotini; Kikas, Eve; Wong, Bernard P. H.; Stanculescu, Elena; Basnett, Julie; Duck, Robert; et al.
Abstract : Background: A comprehensive understanding of the contextual factors that are linked to student engagement requires research that includes cross‐cultural perspectives. Aims: This study investigated how student engagement in school is associated with grade, gender, and contextual factors across 12 countries. It also investigated whether these associations vary across countries with different levels of individualism and socio‐economic development. Samples: The participants were 3, 420 7th, 8th, and 9th grade students from Austria, Canada, China, Cyprus, Estonia, Greece, Malta, Portugal, Romania, South Korea, the United Kingdom, and the United States. Methods: The participants completed a questionnaire to report their engagement in school, the instructional practices they experienced, and the support they received from teachers, peers, and parents. Hierarchical linear modelling was used to examine the effects at both student and country levels. Results: The results across countries revealed a decline in student engagement from Grade 7 to Grade 9, with girls reporting higher engagement than boys. These trends did not vary across the 12 countries according to the Human Development Index and Hofstede's Individualism Index. Most of the contextual factors (instructional practices, teacher support, and parent support) were positively associated with student engagement. With the exception that parent support had a stronger association with student engagement in countries with higher collectivism, most of the associations between the contextual factors and student engagement did not vary across countries. Conclusions: The results indicate both cultural universality and specificity regarding contextual factors associated with student engagement in school. They illustrate the advantages of integrating etic and emic approaches in cross‐cultural investigations.